Strategi Kepemimpinan Entrepreneurship Kiai dalam Eskalasi Kemandirian Santri melalui Pendidikan Terpadu di Pesantren - Sofyan Tsauri; Finadatul Wahidah (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2023)
Islamic boarding schools are idealized as institutions that can effectively provide answers to these developments. The history of pesantren has gone through various social, cultural, and economic challenges in a cosmopolitan society. One of the elements that are the central control of the pesantren is the leadership of the kiai. Kyai leadership is a topic that has received a lot of attention from pesantren researchers because it is one of the factors that determine development. The existence of the kiai not only leads, and motivates but also compiles, manages, and develops the entrepreneurship curriculum. Entrepreneurial leadership is seen as a strong factor in improving the performance of administrators. Visionary leadership is believed to be an important part of the growth and improvement of pesantren performance in the field of economic development. Entrepreneurial leadership knows how to put ideas into action through effective management, and clear strategy. This research focuses on the strategies applied by the kiai and the independence of santri entrepreneurship. The location of this research was carried out at the Jember Nurul Qarnain Islamic Boarding School and Al-Ittifaq Bandung Islamic Boarding School with a qualitative approach with a multi-case design and data analysis used was Miles and Huberman data analysis. The results of this study are in developing santripreneurs by implementing integrated education. Nurul Qarnain Islamic Boarding School and Al-Ittihad Islamic Boarding School combine knowledge and economic endeavors. The integrated education strategy includes increasing the academic skills of teaching staff, bringing in experts in the field of agribusiness, establishing partnerships with other institutions, and managing agribusiness funding. Educational methods include mastery of religious sciences, religious practices, and internships in Islamic boarding schools' independent economic businesses. Pesantren diidealkan sebagai institusi yang secara efektif memberikan jawaban atas perkembangan tersebut. Historia pesantren telah melewati berbagai tantangan sosial, budaya dan ekonomi masyarakat yang kosmopolitan. Salah satu unsur yang menjadi pusat pengendali pesantren adalah kepemimpinan kiai. Kepemimpinan kiai merupakan topik yang mendapat banyak perhatian pengkaji pesantren, karena merupakan salah satu faktor yang menentukan pengembangan. Keberadaan kiai tidak hanya memimpin, memotivasi, tetapi juga menyusun, mengelola dan mengembangkan kurikulum enterpreneurship. Kepemimpinan entrepreneurship dipandang sebagai faktor yang kuat meningkatkan kinerja pengurus. Kepemimpinan visioner diyakini sebagai bagian penting dalam pertumbuhan dan peningkatan kinerja pesantren dalam bidang pengembangan ekonomi. Kepemimpinan entrepreneurship mengetahui bagaimana mewujudkan ide melalui manajemen yang efektif, strategi yang jelas. Penelitian ini fokus kepada strategi yang diterapkan oleh kiai dan kemandirian entrepreneurship santri. Lokasi penelitian ini yakni dilakukan di Pesantren Nurul Qarnain Jember dan Pesantren Al-Ittifaq Bandung dengan pendekatan kualitatif dengan desain multikasus dan analisis data yang digunakan adalah analisis data Miles and Huberman. Hasil dari penelitian ini adalah dalam mengembangkan santripreneur dengan menerapkan pendidikan terpadu. Pesantren Nurul Qarnain dan Pesantren Al-Ittihad memadukan antara ilmu dan usaha ekonomi. Strategi pendidikan terpadu meliputi peningkatan kecakapan akademis tenaga pengajar, mendatangkan pakar dalam bidang agribisnis, menjalin kerjasama dengan lembaga lain, dan pengelolaan pendanaan agribisnis. Metode pendidikan meliputi penguasaan ilmu-ilmu agama, praktik keberagamaan dan magang usaha ekonomi mandiri milik pesantren.